Myoma-associated pain frequency and intensity: a retrospective evaluation of 1548 myoma patients. (April 2016) - David, Matthias; Pitz, Clara Maria; Mihaylova, Adriana; Siedentopf, Friederike
Abstract: Objective: To analyze the possible relation between symptoms (especially pain) reported by myoma patients and objective features of their myomas as determined by ultrasound. Specifically: (1) What is the frequency and intensity of myoma-related pain? (2) Does the pain intensity depend on the number, size, or location of the myomas? (3) Is there any correlation between premenstrual pain, menstrual pain, and pain during sexual intercourse? Study design: A retrospective analysis of data from a patient questionnaire and ultrasound exams, collected from February 2009 until January 2013 at the myoma clinic of a university hospital in a large European city. The study analyzed data from 1548 myoma patients. Patients completed a 0–10 Likert scale questionnaire about their symptoms. The number, size, and location of myomas were determined from ultrasound exams. Results: The three most frequent symptoms reported were hypermenorrhea, dysmenorrhea, and premenstrual pain. There was no statistically significant relationship between premenstrual pain or pain during sexual intercourse on the one hand and the number, size, or location of myomas on the other hand. For women with severe dysmenorrhea (Likert-scale scores of 8–10), submucosal myomas were significantly more frequent than all other myoma locations ( p = 0.01). Severe dysmenorrhea (Likert-scale scores of 8–10) was reported by a significantly ( p < 0.001) greater portion of the women whose largest myoma had a largest diameter of <5 cm than by the women whose largest myoma had a diameter ≥5 cm. The number of myomas did not have a significant influence on the dysmenorrhea intensity. The three types of pain (premenstrual, menstrual, and/or during sexual intercourse) had moderate pairwise correlations ( ρ values from 0.304 to 0.542) that were all statistically highly significant ( p < 0.001). Conclusion: Myoma-associated pain is, alongside hypermenorrhea, the most frequent problem reported by the affected patients. Unlike premenstrual pain and pain during sexual intercourse, the intensity of menstrual pain is clearly dependent on the location and size of the largest myoma. Further research is needed to better understand the degree to which the pain reported by the patients is due to features of the myomas versus other possible factors.